Analisis Proses Pembuatan Surat Eligibilitas Peserta BPJS Di RSUD Dr. H. Moch. Ansari Saleh Banjarmasin Tahun 2024 - Rabiatul Adawiah; Soraya (CV. ITTC INDONESIA, 2024)
The process of making a BPJS Participant Eligibility Letter begins with the collection of the necessary documents, such as the patient's identity, BPJS number, and other supporting documents. The documents are then verified by BPJS officers to ensure the validity of the information and the completeness of the documents. One of the important steps in this process is the verification of participant data, including checking the validity of the BPJS number and the existence of the participant in the BPJS database. The process of making a BPJS participant eligibility letter also involves checking the participant's membership status, whether they are still active or not, as well as the eligibility of the participant to get health services covered by BPJS